2018
DOI: 10.3390/app8122403
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interfacial Ge and RF-Bias on the Microstructure and Stress Evolution upon Annealing of Ag/AlN Multilayers

Abstract: The present study addresses the structural stability and mass outflow of Ag 10 nm/Ge 1 nm/AlN 10 nm nanomultilayers (NMLs) during thermal treatments in different atmospheres (Ar and air). The nanomultilayers were obtained by magnetron sputtering under different deposition conditions (with and without the RF (Radio-Frequency)-bias application). The microstructure of the as-deposited and thermally treated NMLs were analyzed by XRD and SEM techniques, deriving morphology, microstructure and internal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Material coating systems, in particular, nanostructured coatings, so-called nanomultilayers (NMLs), show unique properties and offer new opportunities for many applications. Very recently, NML coatings of brazing fillers alternated by a functional barrier (i.e., Ag/AlN, Cu/AlN, Cu/W, Al/AlN, AgCu/AlN, and AlSi/AlN) were designed to serve as low-temperature brazing nanofillers for packaging and assembling miniaturized devices and heat-sensitive components at ever-reduced processing temperature [48][49][50][51][52][53][54]. Fast diffusion and extensive mass transport were observed in these nanomultilayers at temperatures much below the melting temperature of the bulk brazing filler (T > 250 • C), and they were exploited for joining technology applications [48,[50][51][52][53].…”
Section: Micro/nanojoining For Microelectronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Material coating systems, in particular, nanostructured coatings, so-called nanomultilayers (NMLs), show unique properties and offer new opportunities for many applications. Very recently, NML coatings of brazing fillers alternated by a functional barrier (i.e., Ag/AlN, Cu/AlN, Cu/W, Al/AlN, AgCu/AlN, and AlSi/AlN) were designed to serve as low-temperature brazing nanofillers for packaging and assembling miniaturized devices and heat-sensitive components at ever-reduced processing temperature [48][49][50][51][52][53][54]. Fast diffusion and extensive mass transport were observed in these nanomultilayers at temperatures much below the melting temperature of the bulk brazing filler (T > 250 • C), and they were exploited for joining technology applications [48,[50][51][52][53].…”
Section: Micro/nanojoining For Microelectronicsmentioning
confidence: 99%
“…The overall understanding of the effect of these parameters on the NML behavior in various service conditions is crucial for proper NML design. Using the example of Ag/Ge/AlN nanomultilayers, Cancellieri et al [54] showed that the stress state of as-deposited NML structures can be controlled by the substrate bias during the deposition process or by the modification of the layer interfaces through the small addition of a second material. In this way, the thermal evolution and stability of the nanomulitlayers, as well as the directional mass outflow of the brazing filler material, can be tuned.…”
Section: Micro/nanojoining For Microelectronicsmentioning
confidence: 99%
“…Another approach is the development of nanomultilayered composite/hybrid joining materials, based on the concept emerged in the last decade [13,23,24]. This type of multilayer consists of a periodic repetition of a few nanometer thick metal (or alloy) layers and chemically inert barriers (usually oxides, nitrides, or refractory metals) [25,26]. The purpose of the construction is to preserve the nanothickness of the metal layers up to their melting point by separating them with the diffusion barriers.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the nanoscale, poor adhesion of silver to commonly used substrates such as ultra-smooth fused silica or sapphire results in a rough metal-free surface, which increases the scattering losses of the metal film. To tackle this problem, a number of approaches have been proposed, the most prominent being the use of wetting materials exhibiting good adhesion to both silver and the substrate [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The greatest reduction of surface roughness-up to an order of magnitude-is observed when the substrate is wetted with a~2-nm-thick layer of germanium prior to the deposition of silver [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…Instead of covering the silver layer with a material which exhibits grain boundary diffusion within silver, we introduce another layer below germanium, which is made of gold. Germanium has been proven to segregate within the nanolayers of both silver and gold [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], as Ag and Au exhibit many crucial similarities, like their atomic radius and lattice constant. However, the free enthalpy of the segregation process is influenced by many quantities in which silver and gold differ-e.g., bulk modulus, shear modulus and surface energies [28,42].…”
Section: Introductionmentioning
confidence: 99%